2020
DOI: 10.1016/j.isci.2020.100835
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA CISAL Inhibits BRCA1 Transcription by Forming a Tertiary Structure at Its Promoter

Abstract: Cisplatin-based neoadjuvant chemotherapy has been shown to improve survival in patients with squamous cell carcinoma (SCC), but clinical biomarkers to predict chemosensitivity remain elusive. Here, we show the long noncoding RNA (lncRNA) LINC01011, which we termed cisplatin-sensitivity-associated lncRNA (CISAL), controls mitochondrial fission and cisplatin sensitivity by inhibiting BRCA1 transcription in tongue SCC (TSCC) models. Mechanistically, we found CISAL directly binds the BRCA1 promoter and forms an RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…One possible explanation for association between high BRCA1 expression and poor prognosis, high BRCA1 would protect HCC from further DNA damage, which might promote resistance to chemotherapeutics. In tongue squamous cell carcinoma, lncRNA CISAL inhibited BRCA1 transcription by forming a tertiary structure at its promoter and associated favorable neoadjuvant chemosensitivity (Fan et al, 2020), which was consistent with our conjecture. Wang et al (2018) performed a systematic analysis to uncover the expression profiles and prognostic values of BRCA1 in digestive system cancers.…”
Section: Discussionsupporting
confidence: 91%
“…One possible explanation for association between high BRCA1 expression and poor prognosis, high BRCA1 would protect HCC from further DNA damage, which might promote resistance to chemotherapeutics. In tongue squamous cell carcinoma, lncRNA CISAL inhibited BRCA1 transcription by forming a tertiary structure at its promoter and associated favorable neoadjuvant chemosensitivity (Fan et al, 2020), which was consistent with our conjecture. Wang et al (2018) performed a systematic analysis to uncover the expression profiles and prognostic values of BRCA1 in digestive system cancers.…”
Section: Discussionsupporting
confidence: 91%
“…(4) It was found that increased expression level of LINC01063 was significantly correlated with metastasis and poor prognosis of the patients with colon adenocarcinoma [ 31 ]. (5) Fan et al found that LINC01011 controlled cisplatin sensitivity and mitochondrial fission via suppressing BRCA1 transcription in a tongue SCC model [ 32 ]. (6) LINC02381 might have inhibiting effects on CRC tumorigenesis partly through regulating PI3K pathway [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that current studies on lncRNA mechanisms converge on establishing intermolecular interactions with other molecules, such as proteins, DNA, and other RNAs, it is essential to elucidate the lncRNA-protein and lncRNA-DNA interactions they engage in. Recent studies [171,172] have reported that lncRNAs function by forming RNA-DNA triple helixes with DNAs. In tongue squamous cell carcinoma, lncRNA CISAL can be tethered to the gene promoter through RNA-DNA triple helix formation, spatially sequestering transcription factors away from DNA-binding sites and restraining transcription of tumor suppressor genes [171].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recent studies [171,172] have reported that lncRNAs function by forming RNA-DNA triple helixes with DNAs. In tongue squamous cell carcinoma, lncRNA CISAL can be tethered to the gene promoter through RNA-DNA triple helix formation, spatially sequestering transcription factors away from DNA-binding sites and restraining transcription of tumor suppressor genes [171]. LncRNA Fendrr can form RNA-DNA triple helixes in the promoter region of developmental genes and then serve as an anchor to recruit the histone-modifying protein PRC2 [172].…”
Section: Future Perspectivesmentioning
confidence: 99%